Nanoparticles-Assisted Stem Cell Therapy for Ischemic Heart Disease - Kai Zhu; Jun Li; Yulin Wang; Hao Lai; Chunsheng Wang (Hindawi Limited, 2016)
Stem cell therapy has attracted increasing attention as a promising treatment strategy for cardiac repair in ischemic heart disease. Nanoparticles (NPs), with their superior physical and chemical properties, have been widely utilized to assist stem cell therapy. With the help of NPs, stem cells can be genetically engineered for enhanced paracrine profile. To further understand the fate and behaviors of stem cells in ischemic myocardium, imaging NPs can label stem cells and be tracked in vivo under multiple modalities. Besides that, NPs can also be used to enhance stem cell retention in myocardium. These facts have raised efforts on the development of more intelligent and multifunctional NPs for cellular application. Herein, an overview of the applications of NPs-assisted stem cell therapy is given. Key issues and future prospects are also critically addressed.